2018
DOI: 10.1177/2325967118758602
|View full text |Cite
|
Sign up to set email alerts
|

Male Sex, Decreased Activity Level, and Higher BMI Associated With Lower Completion of Patient-Reported Outcome Measures Following ACL Reconstruction

Abstract: Background:Patient-reported outcome (PRO) surveys have become increasingly important in both improving patient care and assessing outcomes.Purpose/Hypothesis:The purpose of this study was to evaluate which variables are associated with compliance with completing PRO surveys in patients who have undergone anterior cruciate ligament reconstruction (ACLR). The authors hypothesized that older patient age and longer time since ACLR would be associated with lower completion rates of PRO surveys preoperatively and at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Cotter et al reported similar findings of lower survey completion among patients with lower activity levels after anterior cruciate ligament reconstruction. 19 The reasons for this association are unknown, but it seems probable that more active patients have higher energy levels.…”
Section: Discussionmentioning
confidence: 99%
“…Cotter et al reported similar findings of lower survey completion among patients with lower activity levels after anterior cruciate ligament reconstruction. 19 The reasons for this association are unknown, but it seems probable that more active patients have higher energy levels.…”
Section: Discussionmentioning
confidence: 99%
“…One study of anterior cruciate ligament reconstruction included 313 patients, while another in shoulder arthroscopy included 143 patients. 14 , 15 The current study included 225 patients, and we must consider the possibility of type II error due to the study being underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…The most cited demographics for PROM noncompletion following elective orthopaedic procedures are male sex, younger age, and non-White race. 5 , 14 , 16 , 17 , 18 , 19 Although these are commonly cited, a recent study analyzing 9 factors concluded no single patient characteristic can accurately predict loss to follow-up. 20 This study failed to replicate the results of previous orthopaedic studies; however, one publication specific to shoulder arthroscopy did not find differences in PROM compliance, according to patient age or gender.…”
Section: Discussionmentioning
confidence: 99%
“…Social determinants ranging from the structure and systems level (e.g., federal or state regulations), community level (e.g., policies or built environment), institutional level (e.g., schools or healthcare administration), interpersonal level (e.g., support systems), to the individual level (e.g., health behaviors or beliefs) are interconnected and impact the health achievement of individuals ( 9 ). Although individual characteristics such as sex, BMI, or age are associated with PROM completion ( 10 , 11 ), no study has simultaneously evaluated upstream system-level factors and individual-factors associated with PROM completion. In this paper, we performed an observational study with a retrospective chart review to examine individual (parent/child), and clinic factors associated with parental completion of a locally developed PROM, the Early Healthy Lifestyles (EHL) questionnaire, at Geisinger pediatric care clinics between 2016 and 2020.…”
Section: Introductionmentioning
confidence: 99%